LAND WRITINGS : excursions in the footprints of edward thomas. - Riding, James (CAMBRIDGE SCHOLARS PUBLIS, 2017)
Whilst out walking one day in the shade at the age of thirty-six, with the First World War looming, Edward Thomas decided to become a poet. In the few years that followed, believing he belonged nowhere, he tramped across rolling chalk downland, stitching himself to the landscape. Gently slanting from the door of his stone cottage, the South Downs - a range of chalk hills that extend across the southeastern coastal counties of England from Hampshire in the west to Sussex in the east - became day by day the mainspring of his poetry. As a perennial poet and essayist of the South Downs, Edward Tho.